A Labor Market Assessment of Nurses and Physicians in Saudi Arabia : Addressing Future Imbalances between Need, Supply, and Demand - Alghaith, Taghred (World Bank, Washington, DC, 2021)
Strengthening the health workforce in Saudi Arabia is central to ongoing reform efforts in the country and to the changing business priorities in the health sector and beyond. Saudi Arabia’s Vision 2030 aims to increase the size and performance of the Saudi health workforce to meet changing population needs and to achieve ambitious social and economic targets and goals. This book presents rigorous, empirical, and quantitative evidence to support national-level strategic planning efforts on human resources for health in Saudi Arabia. The book, a collaborative effort between the Saudi Health Council and the World Bank, is a first to anticipate and quantify projected future labor market imbalances of nurses and physicians in Saudi Arabia and to identify solutions to close those gaps. Drawing on the latest principles and modeling techniques in epidemiology and economics, the book forecasts future imbalances between epidemiological need and labor market supply and demand. It culminates in a set of policy recommendations to improve the availability, distribution, and performance of Saudi nurses and physicians. The book is expected to be of interest to health workforce planners and health systems researchers working in Saudi Arabia and beyond.